Glazialmorphologische Probleme in den Hochgebirgen Vorderasiens - Klaer, Wendelin (ERDKUNDE, 1969)
On the basis of various observations in the mountains of subtropical latitudes in the Near East, the importance of climatic-genetic factors for the morphology of high mountain ranges is discussed. It can be shown that, in summer-drought subtropical latitudes, ’radiation’ is the climatic element which has the most influence on the morphological development of the highest mountain ranges. Radiation alone overwhelmingly and dominantly influences the total geomorphic process in ’nival’ and ’subnival’ mountain zones in a way undemonstrable in any other climatic zone. High radiation intensity forces ’nival’ processes to operate at a height of more than 1500 m over the climatic snowline on south-facing slopes and the same reason adds to the effectiveness of solifluction processes (e. g. Elburz Mountains). The situation on north-exposed slopes is quite the reverse. Because of the virtual elimination of radiation, which here touches slope surfaces with only a very shallow angle of impact, other ablation-hindering climatic factors gain in morphological importance. Glaciers more than 1000 m below the climatic snow-line are no rare occurrence (e. g. Artos Dagh). Glacial slope formation, despite greater continentality, is depressed in the north-exposed area and solifluction slope formation in the south-exposed area is encouraged, despite greater maritime influence (e. g. Toros Dagh, Artos Dagh). In this way the ’subnival’ mountain range on the southern facet with its strong solifluction influence (level slope formation) approaches in height the ’nival’ mountain range on the northern facet which is distinguished by its well-developed glacial forms. It is from this situation that assymetrical ridge or valley-side formation, in the form almost exclusively found in the mountains of subtropical latitudes, arises.